Implications for Cultural Sharedness When Sharedness Is Not Assumed. (January 2014) - Wan, Ching; Lu, Chieh
Schwartz (2013) proposed a model of societal culture in which societal culture is conceptualized as a latent construct that exists outside of individuals. With such conceptualization, Schwartz argued that the assumption of cultural sharedness would not be necessary for research on cross-national differences of personal values. Interestingly, the removal of the assumption of cultural sharedness can generate new research questions that can further the field's understanding of the nature and function of cultural sharedness. This commentary explores several of these possibilities.